2015
DOI: 10.1002/ejoc.201500812
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β‐Substituted meso‐Tetraaryl‐21,23‐dithiaporphyrins by Heck Reaction

Abstract: Keywords: Synthetic methods / Porphyrinoids / Macrocycles / Electronic effects meso-Tetraphenyl-21,23-dithiaporphyrin was selectively monobrominated at one β-pyrrolic position in good yields. This dithiaporphyrin was then functionalized by Heck reaction with styrene derivatives containing different electronic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…CDA type reactions may occasionally occur spontaneously, as evidenced by a recent report by Cavaleiro, de Souza, Neves et al, who observed formation of 355.2 under Heck-type conditions (Scheme ). The UV–vis spectrum of 355.2 exhibited a broad and split Soret band, which was ascribed to the high deformation of the macrocycle caused by its five-membered ring.…”
Section: Macrocyclic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDA type reactions may occasionally occur spontaneously, as evidenced by a recent report by Cavaleiro, de Souza, Neves et al, who observed formation of 355.2 under Heck-type conditions (Scheme ). The UV–vis spectrum of 355.2 exhibited a broad and split Soret band, which was ascribed to the high deformation of the macrocycle caused by its five-membered ring.…”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“… a Reagents and conditions: (a) styrene, Pd­(OAc) 2 , K 2 CO 3 , PPh 3 , DMF/toluene (1:1, v/v), reflux, 1 h. …”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“…Having this in mind and following our interest in the development of synthetic approaches to prepare novel porphyrin derivatives [2830], we decided to explore the palladium-catalyzed cross-coupling reaction of meso -tetraphenyl-β-bromoporphyrin using N -tosylhydrazone derivatives with different electronic features for the preparation of new β-alkenyl-type porphyrin derivatives. This approach can provide interesting compounds with potential biological properties or might become important templates for further functionalization procedures (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%